Answer:
(1, -2)
Explanation:
So we can work straight away
The elimination method deals with eliminating one variable so that you can find the other, then substituting that back in to find the one we eliminated originally. So, let's add our two equations together:
9x - 3y = 15
+ 3x + 3y = -3
12x = 12
So now that we've reached a new equation, 12x = 12, we can divide both sides by 12 and get that:
x = 1
Substituting this back into the second equation (though you could sub it into either one):
3(1) + 3y = -3
3 + 3y = -3
3y = -6
y = -2
Therefore, x = 1 and y = -2, also represented as (1, -2)
Hope this helps!